Extended Abstracts of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3334480.3383078
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Privacy Relevant Information Affect App Market Choice?

Abstract: While in most countries, Google Play and Apple App Store dominate, Chinese mobile phone users can choose among dozens of different app markets, which differ greatly in the information presented. This makes the Chinese mobile ecosystem a unique case study for investigating whether users actively choose app markets that conform to their preferences. We investigated this question in a survey of 200 Chinese users aged 18-49. Scenarios covered apps that require disclosure of different types of sensitive information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In fact, most of these projects are either partially or completely fail. For instance, it has been found that there were weaknesses when it comes to the process of establishing the e-government applications which promotes the use of online service [21] around Iraq. Moreover, according to United Nations survey in 2014, it has been claimed that the progress in the completion of e-government in Iraq has been slow and recently the rank has been steadily decreasing.…”
Section: Ict In Iraqmentioning
confidence: 99%
“…In fact, most of these projects are either partially or completely fail. For instance, it has been found that there were weaknesses when it comes to the process of establishing the e-government applications which promotes the use of online service [21] around Iraq. Moreover, according to United Nations survey in 2014, it has been claimed that the progress in the completion of e-government in Iraq has been slow and recently the rank has been steadily decreasing.…”
Section: Ict In Iraqmentioning
confidence: 99%